Synthesis and mesomorphic properties of schiff base esters with different terminal substituents / Chong Yee Ting - Chong , Yee Ting (2018)
Liquid crystal is a class of fascinating material showed unique properties such as thermochromism and photochromism which allowed applications in display devices, anisotropic networks, photoconductors and semiconductor materials. The study in liquid crystal science led to development of understanding the mesomorphic properties with small changes in terminal groups, carbon chains and incorporated heteroatom into mesogenic units. Four series of Schiff base esters comprising either thiophene or aromatic rings were successfully prepared via imination, and Steglich esterification which was widely reported. The chemical structure of the esters was confirmed by Fourier-transform infrared spectroscopy (FTIR), proton and carbon nuclear magnetic resonance (1H and 13C NMR) together with CHN elemental analysis. The mesomorphic properties were determined using differential scanning calorimetry (DSC) and polarized optical microscopy (POM). DSC results revealed that most of the prepared esters exhibited multi-transition either in heating or cooling process or both. This had evidenced by the presence of several phase transition peaks between crystals and isotropic liquid. The liquid crystal textures were later confirmed with the POM analysis by comparing with the reported literature. First series (nSB-R) comprising different terminal groups (R = CH3, OCH3 and N(C2H5)2). Methoxy group series showed nematogenic properties whereas methyl group series displayed both nematic and smectic A or B phases for its compound, 14SB-CH3. However, diethylamino group series showed direct isotropization behavior. The results suggested that a bulky substituent may disrupt the mesogen arrangement that enable liquid crystal mesophase. A small non-polar group such as methyl group was minimized the steric hindrance between the molecules and allowed them to be orientated and interacted closer. Second series (nSHB-OCH3) comprising the additional lateral hydroxy group of previous series. The DSC and POM results revealed that additional hydroxy group increased liquid crystal phase stability and enhanced lateral interaction. Although methoxy group reported as one of the terminal groups which favors in nematic phase, but the impact of lateral hydroxy group was significant and allow the lamellar packing smectic A phase. In third series, only OBSB-Cl and OBSB-OCH3 showed the liquid crystal properties while the rest are non-mesogenic. The results displayed that a bulky substituent at the terminal flexible chain will increase the steric hindrance effect between the molecules and diminished the mesomorphic properties. The present of heteroatom in fourth series (nAPTP) impacted on its anisotropy and enhanced the phase stability. The heteroatom such as S, O and N significantly impart lateral and/or longitudinal dipoles as it was more polarizable than carbon. Thiophene group reduced the linearity of the molecules and this had enhanced the molecule to tilt with an angle and led to favor in Smectic C phase. The liquid crystal properties are greatly influenced by the small changes in the molecular architecture and this will lead to existence of different mesophase and phase stability.